Crop Yields as Influenced by Run-Off and Soil Moisture Storage - Jain, B L; Singh, R P (Annals of Arid Zone, 2016)
Field trials carried out for four consecutive years, 1974 through ]977, at the CAZRI-Regional Research Station, Pali-Marwar. revealed that microcatchments (run-off plots), irrespective of slopes, provided 50 to 80 per cent additional run-off to the cropped strips (run-on plots). Higher yields of the order of 40 to 60 per cent were obtained in the run-on plots over control, besides relatively higher moisture content in the soil profile.